Analysis of the Effect of Company Size, Audit Quality, and Audit Delay on Audit Size as a Moderating Variable (A Study of Basic Materials Companies Listed on the Indonesia Stock Exchange in 2022-2024) - Maria Martha Sulistiowati; Cherrya Dhia Wenny (LP2M IAIN Palopo, 2025)
This study addresses the increasing issue of audit delays in the Basic Materials sector listed on the Indonesia Stock Exchange during 2022–2024. The research aims to empirically analyze the impact of firm size and audit quality on audit delay, as well as examine the moderating role of Public Accounting Firm (KAP) size. The study employs a quantitative explanatory causal design using secondary data from annual financial statements and audit reports. The population consists of all Basic Materials companies listed during the period, with a purposive sample of 36 companies. Data analysis utilized SPSS 27 with classical assumption tests and moderated multiple regression analysis. Results indicate that audit quality significantly affects audit delay while firm size does not show a significant impact. Moreover, KAP size moderates the relationship between audit quality and audit delay but not between firm size and audit delay. The coefficient of determination shows that the combined variables explain up to 62.8% of the variance in audit delay. The findings highlight the critical role of auditor competence and KAP resources in timely audit completion. The study concludes that improving audit quality and engaging larger KAPs can help reduce audit delays in Indonesia's capital market.